UJI PROLIFERASI TERHADAP SEL MONONUKLEAR DENGAN PENAMBAHAN MADU Tetragonula sp DAN ROYAL JELLY Apis mellifera DI MEDIUM DMEM - Nadia Nurulita (2022)
Mononuclear cells wich contain hematopoietic stem cells have an important role in the world of alternative therapies for various diseases. The medium used to proliferate cells is DMEM with the addition of Fetal Bovine Serum (FBS). However, FBS has ethical and animal welfare concerns, infection hazards and allergies for medical applications. To avoid this, serum-free media is needed, for example by using honey and royal jelly. This study aims to determine the effectiveness of the addition by a combination of Tetragonula sp honey and Apis mellifera royal jelly on mononuclear cell proliferation. This research design used a pure experimental method. Samples were obtained from a healthy person. Mononuclear cells were cultured with two different concentrations of honey and royal jelly (0,1% and 0,05%) and the other two with the same concentrations were added with FBS 10%, and then measured using the MTS assay. The highest proliferation rate was found in honey and royal jelly 0,1% with the addition of FBS 10% and had a significant difference with honey and royal jelly 0,1% (p = 0,000), honey and royal jelly 0,05% (p = 0,000), honey and royal jelly 0,05% + FBS 10% (p = 0,000), and all the media exceeded the proliferation on standardized media with FBS. Media culture with the addition of honey and royal jelly is most optimal at concentration of 0,1%. The addition of FBS components is still needed to optimize the increase in proliferation in honey and royal jelly media. The composition of honey and royal jelly with low concentration can increase the proliferation rate of mononuclear cell. Isolation of proliferative-active ingredients in honey and royal jelly can be used as an alternative to developing an effective and safe substitute for FBS